Analisis Kesehatan Bank Umum Syariah di Indonesia Menggunakan Metode RBBR Tahun 2021-2024 - Arisha Putri Pradita; Vika Diyah Ardiyanti (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the health of Islamic Commercial Banks in Indonesia using four indicators of the Risk-Based Bank Rating (RBBR) method: risk profile (NPF), profitability (ROA), capital (CAR), and good corporate governance (GCG) from 2021 to 2024. A descriptive research approach was employed, utilizing secondary data obtained from the Islamic Banking Statistics reports published by the Financial Services Authority (OJK). Data analysis was conducted by presenting tables and identifying performance trends in each of the main RBBR indicators, namely risk profile (NPF), profitability (ROA), capital (CAR), and good corporate governance (GCG). The results of the study indicate that Islamic Commercial Banks in Indonesia have demonstrated a positive trend across all indicators. The risk profile indicator, represented by Non-Performing Financing (NPF), showed a decline from 2.59% in 2021 to 2.08% in 2024, placing Islamic Commercial Banks in the "healthy" category. The profitability indicator also improved, with Return on Assets (ROA) increasing from 1.55% to 2.07%, reflecting enhanced operational efficiency and moving from a “fairly healthy” to “healthy” condition. In terms of capital, the Capital Adequacy Ratio (CAR) remained consistently high, ranging from 25.30% to 26.28%, indicating a very strong and resilient capital position. Finally, the GCG factor consistently achieved a score of 2, indicating a “good” level of corporate governance implementation. Collectively, these findings conclude that Islamic Commercial Banks in Indonesia were in a sound and stable condition throughout the observation period based on the RBBR assessment, affirming the effectiveness of these principles in ensuring the performance and sustainability of the Islamic banking sector.